2008
DOI: 10.1016/j.vaccine.2008.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Associations between SNPs in toll-like receptors and related intracellular signaling molecules and immune responses to measles vaccine: Preliminary results

Abstract: Toll-like receptors (TLRs) represent the critical "bridge" between innate and adaptive immunity to viral pathogens. We hypothesized that single nucleotide polymorphisms (SNPs) that potentially influence the expression/function of TLRs and their associated intracellular signaling molecules contribute to variations in humoral and cellular immunity to measles vaccine. We genotyped 190 randomly selected subjects (12-18 years old), previously vaccinated with two doses of measles, for known SNPs in TLR 2, 3, 4, 5, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
107
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 30 publications
3
107
2
2
Order By: Relevance
“…The variant allele of TLR5 (rs5744174), which is related to decreased IL-1β and IL-6 mRNA, 23 and increased levels of CCL20 (ref. 24) and IFN-γ 25 were associated with beneficial response to ustekinumab, again indicating that an increased IL-1β level may be unfavorable when treating psoriasis with ustekinumab. However, the variant allele of TLR2 (rs3804099), which is related to high levels of TNF-α, IL-1β and IL-6 and a reduced MYD88 level, 26 was nominally associated with a beneficial response, and this might indicate that not only the level of IL-1β but also the relative abundance of cytokines is crucial for response to ustekinumab treatment.…”
Section: Study Populationmentioning
confidence: 92%
See 1 more Smart Citation
“…The variant allele of TLR5 (rs5744174), which is related to decreased IL-1β and IL-6 mRNA, 23 and increased levels of CCL20 (ref. 24) and IFN-γ 25 were associated with beneficial response to ustekinumab, again indicating that an increased IL-1β level may be unfavorable when treating psoriasis with ustekinumab. However, the variant allele of TLR2 (rs3804099), which is related to high levels of TNF-α, IL-1β and IL-6 and a reduced MYD88 level, 26 was nominally associated with a beneficial response, and this might indicate that not only the level of IL-1β but also the relative abundance of cytokines is crucial for response to ustekinumab treatment.…”
Section: Study Populationmentioning
confidence: 92%
“…For patients treated with ustekinumab, variants related to an increased level of IFN-γ (TLR5 (rs5744174) 25 and TIRAP (rs8177374) 27 ) appears to be associated with a beneficial response. Moreover, the variant allele of IFNG (rs2430561)-conveying high levels of IFN-γ 28,29 -was found to be nominally associated with a beneficial response to ustekinumab.…”
Section: Study Populationmentioning
confidence: 99%
“…A previous study found that individuals heterozygous for TLR3 SNP rs3775291 had a lower immune response to a measles vaccine (5); this was also observed in responders in this study (with IgG responses of Ն2 g/ml). Seven SNPs within the TLR3 gene have been described to be associated with vaccine-induced immunity to viral vaccines (rs6822014, rs11721827, rs13126816, rs3775296, rs5743305, rs1914926, and rs3775291) (5,16). The current work increases the number of SNPs in the TLR3 gene affecting vaccine responses to 10.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, we found rs5744174 TCþCC genotype was associated with elevated risk of GC. The rs5744174 T>C change causes a substitution of Leucine to Phenylalanine at amino acid 616, may likely affect the response of ligand recognition and the following signaling associated with inflammation, thus ultimately contributing to increased risk of GC (47). Further study should be conducted to reveal the functional relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism of TLR5 polymorphism on the H. pylori-associated carcinogenesis is unclear, it may be reasonable that rs5744174 polymorphism could affect the ligand recognition, favoring H. pylori persistence in the stomach. Thus, in those subjects with high-risk genotype and H. pylori infection, increased secretion of proinflammatory cytokines due to persistent H. pylori infection amplify the chronic inflammation and ultimately the development of GC (47,48).…”
Section: Discussionmentioning
confidence: 99%